Implementasi Kebijakan Pemadanan NIK Menjadi NPWP Dalam Meningkatkan Kepatuhan Wajib Pajak Orang Pribadi Di Kantor Pelayanan Pajak Pratama Jakarta Kelapa Gading - Ng Kian Ping; Ahmad Hidayat (Jurnal Pajak Vokasi (JUPASI), 2025)
The implementation of the NIK to NPWP matching policy is motivated by the low compliance of individual taxpayers, especially in registering themselves. With this policy, it will have a significant impact on all Individual Taxpayers in Indonesia. This policy aims to make all Individual Taxpayers in Indonesia from those who previously did not have an NPWP but with this policy, all Individual Taxpayers will have an NPWP and at the same time become registered WP. This study aims to analyze and evaluate the implementation of the policy of matching NIK to NPWP along with the factors that influence it. This research was conducted at KPP Pratama Jakarta Kelapa Gading as the scope. Researchers used descriptive qualitative methods with in-depth interview techniques to 8 people. The result of the research is that the implementation of the NIK to NPWP matching policy at KPP Pratama Jakarta Kelapa Gading has run optimally. This is evidenced by 76 percent of registered Individual Taxpayers have matched NIK to NPWP. However, there are various challenges and problems in implementing this matching policy to be implemented thoroughly. Factors such as the low level of taxpayer compliance, the decline in taxpayer confidence in tax authorities, the socialization of policies that have not been optimally carried out by the population service to the support of resources both human resources and inadequate technology that affect the implementation of the policy. For this reason, the researcher suggests that a synergy of socialization between the ministry of finance and the population service and an increase in the quantity and quality of resources, both human resources and technology, is needed so that the implementation of the NIK to NPWP matching policy at KPP Pratama Jakarta can run optimally. policy aims to make all Individual Taxpayers in Indonesia from those who previously did not have an NPWP but with this policy, all Individual Taxpayers will have an NPWP and at the same time become registered WP. This study aims to analyze and evaluate the implementation of the policy of matching NIK to NPWP along with the factors that influence it. This research was conducted at KPP Pratama Jakarta Kelapa Gading as the scope. Researchers used descriptive qualitative methods with in-depth interview techniques to 8 people. The result of the research is that the implementation of the NIK to NPWP matching policy at KPP Pratama Jakarta Kelapa Gading has run optimally. This is evidenced by 76 percent of registered Individual Taxpayers have matched NIK to NPWP. However, there are various challenges and problems in implementing this matching policy to be implemented thoroughly. Factors such as the low level of taxpayer compliance, the decline in taxpayer confidence in tax authorities, the socialization of policies that have not been optimally carried out by the population service to the support of resources both human resources and inadequate technology that affect the implementation of the policy. For this reason, the researcher suggests that a synergy of socialization between the ministry of finance and the population service and an increase in the quantity and quality of resources, both human resources and technology, is needed so that the implementation of the NIK to NPWP matching policy at KPP Pratama Jakarta can run optimally.